KEARIFAN LOKAL KAOMBO HAMOTA (KAOMBO) DI DESA BURANGASI KECAMATAN LAPANDEWA KABUPATEN BUTON SELATAN - Risnawati Risnawati; Wa Ode Sifatu; La Janu (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2019)
This study aims to reveal the community's compliance with the local wisdom of Kaombo Hamota in the Burangasi community in South Buton Regency. The underlying theory is Geertz's thought of